The Effect of Prophetic Leadership, Organizational Culture on Employee Engagement At sufism-based Islamic Boarding School - Irfan Budiono; Hamidah Hamidah; Mahmuddin Yasin (AIBPM Publisher, 2019)
Pesantren is the oldest Islamic education institution in Indonesia and even in the world. The pesantren has become a very rapidly developing religious education institution. Employee engagement in pesantren is very rarely studied in Indonesia. The purpose of this study was to determine the effect of prophetic leadership and organizational culture on employee engagement in Sufism-based Islamic boarding schools. This study used 230 employees in sufism-based islamic boarding schools. The results show that prophetic leadership has a significant and positive effect on employee engagement. Organizational culture also has a significant and positive effect on employee engagement. The implication of this study shows that prophetic leadership has a great influence on employee engagement in sufism based Islamic boarding schools.